Spice Culture in Java as a Revitalization of Ancient Spice Pathways and Future Progress - M Baiquni (Javanologi: International Journal of Javanese Studies, 2023)
Java is a rich island originating from the archipelago, a large country that has various contents in it. Inside Borobudur Temple, there are neatly engraved reliefs, which tell various events or stories about teachings for mankind. One of the reliefs depicts a sailor sailing and the presence of merchandise, one of which is spices. The history of the magnitude of the spice route and with the development of the spice trade, several positions have also emerged regarding the superior spice commodities in each region of the archipelago, including the following; Java, Maluku, Banda Island, and others. To strengthen the spice path in this modern era, various efforts were made, one of which was this research. Using literature study methods and peer discussions, data are produced, including; 1. Maritime History of Java and the Archipelago, Commodities, and Spice Routes; 2. The Influence of Javanese Civilization and the Center of the Nusantara Spice Line; 3. Form of Activities and Strengthening of Spice Pathways in Java; and 4. Javanese spices, dishes, drinks, and other spices. These forms are expected to be able to be a successful step in the revitalization of ancient spice pathways and future progress.Keywords: Java, Spice Line, revitalization, future progress